Physico-chemical features and membranolytic activity of dust from low or no crystalline silica engineered stone with implications for toxicological assessment - Chandnee Ramkissoon; Cristina Pavan; Jasmine Rita Petriglieri; Marianna Fimiani; Dino Pisaniello; Sharyn Gaskin; Francesco Turci (Scientific Reports)
Abstract The re-emergence of silicosis among engineered stone (ES) workers has prompted the development of low- to no-crystalline silica (SiO2) ES products, marketed as safer alternatives to traditional high-SiO2 ES. However, the composition of these new materials—often incorporating recycled minerals, binders, and pigments—remains complex and poorly characterized in terms of potential health risks. This study assessed the physico-chemical properties and membranolytic activity of dusts generated by mechanical processing of five ES samples (ranging from 90 to 0 wt% SiO2) and a natural stone as comparison. Dusts were analyzed for particle size distribution, mineralogy, morphology and zeta potential. A standard membranolysis assay was used to assess relative cytotoxicity. Dusts from new ES slabs contained lower quartz and cristobalite levels (23 to 0 wt%) than traditional ES, with crystalline silica replaced predominantly by silicates, aluminosilicates, amorphous phases, or gibbsite. Untreated ES dusts showed little membranolytic activity. However, after heating to remove organic binding resins, a high membranolytic activity was observed for traditional ES, and to a lesser degree for low-SiO2 ES. No activity was observed in no-SiO2 ES, composed primarily of gibbsite. Our findings suggest that reducing crystalline silica content may mitigate certain toxicological risks. However, the diverse and evolving composition of alternative ES products warrants ongoing toxicological evaluation.